EVALUATING THE EFFECTIVENESS OF TREATMENT METHODS FOR REFRACTIVE AMBLYOPIA IN CHILDREN - Boboeva Ra’nо Rakhimovna (Educational Research in Universal Sciences, 2023)
In three cases, in the treatment of refractive amblyopia in the children’s department of the Bukhara Regional Ophthalmological Hospital, the device MACDEL-08 "Speckle" was used and its results were studied. 35 patients aged 7-18 years were examined in the outpatient clinic. Examination of children was carried out according to standard plans, and groups of outpatients used methods of lymphostimulation, laser stimulation. The pre- and post-treatment results were analyzed to evaluate treatment outcomes.